Preferences of speech and language therapists for telepractice in the COVID-19 pandemic and factors affecting their acceptance of the delivery model - Cangi, Mehmet Emrah; Yaşa, İbrahim Can; Işıldar, Ayşe (The European Research Journal, 2021)
Objectives: With the COVID-19 pandemic, telepractice became a great option in speech-language therapy services, as in many healthcare utilities. However, the transition to this service model did not occur at a similar rate for every clinician. Therefore, this study aimed to determine the experiences, preferences and factors affecting the acceptance of speech-language therapists (SLT) regarding telepractice in Turkey. Methods: Sixty-seven SLTs were presented with a questionnaire that addressed the professional tendencies, experiences and views on telepractice of them. Descriptive statistics regarding the preferences and experiences of SLTs were calculated. Moreover, factors that might be related to the number of sessions they held at the pandemic were examined with the Chi-squared test. Results: The speech-language disorders that SLTs find the most suitable for telepractice were fluency disorders, voice disorders and speech sound disorders. Groups that SLTs deemed most suitable for receiving telepractice in terms of age were 12-21, 22-64 and 7-11, respectively. A significant relationship was found between the frequency of online meetings and telepractice sessions before the pandemic and the number of sessions during the pandemic. Furthermore, a significant relationship also was found between satisfaction with using clinician skills in telepractice and the number of telepractice sessions during the pandemic. Conclusions: The importance of the first experiences of SLTs in the acceptance of the delivery method emerged. The necessity of in-service trainings and exemplary models to improve attitudes emerged. With these trainings, ensuring security, standardizing practices and increasing qualified services will be provided as well.